Visual system involvement in selected zoonotic diseases. I. Ocular toxocarosis - Kocięcki, Jarosław; Kocięcka, Wanda (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
The paper is presenting the selected problems regarding clinical pathology of ophthalmic toxocariasis, as well as methods of its diagnosis, especially immunodiagnosis. The outline of contemporary treatment of this entity is also presented. The data involves the description of Toxocara's life development cycle and data regarding epidemiology of this zoonosis as well.